Le contrat d’embouchure du delta du Pô : un nouveau défi pour la gestion participative du territoire - Marina Bertoncin; Pierpaolo Faggi; Andrea Pase; Daria Quatrida (Développement Durable et Territoires)
The Po Delta is located at the eastern end of a territory that inherits whatever happens upstream in the most populated and industrialized area of Italy: the basin of the River Po. In this context, the Consorzio di Bonifica (the Land Reclamation Consortium) has proposed the activation of a "contract of mouth".Compared to the national and international experiences of rivers contracts, this initiative proposes two aspects of innovation. The first concerns the actor developing the process. In the Po Delta is a public-private actor as is the Consorzio di Bonifica and not, as has happened in the majority of national experiences, the State which manages the process through the Provinces. The second concerns the definition of the borders of the "contract of mouth". How does one define the "mouth" in this area ? The question does not concern so much the defining of natural boundaries but rather determining which actors could be taken into consideration.